2012
DOI: 10.1007/s10059-012-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

Olfactomedin 4 Suppresses Tumor Growth and Metastasis of Mouse Melanoma Cells through Downregulation of Integrin and MMP Genes

Abstract: Olfactomedin 4 (OLFM4) is highly expressed in gastrointestinal cancers and has an anti-apoptotic function. The roles of OLFM4 in tumor growth and metastasis and how it functions in these processes remain elusive. We investigated the function of OLFM4 in tumor growth and metastasis using B16F10 mouse melanoma cells as an experimental system. Our results showed that OLFM4 had no positive effect on cell viability or cell cycle progression in B16F10 cells. However, it significantly suppressed the tumorigenicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
2
25
1
Order By: Relevance
“…The results from the present study indicated that plasma OLFM4 levels in breast cancer patients were associated with histological tumor differentiation. High plasma OLFM4 levels were detected in patients with high histological grade, which was consistent with data from previous studies on pancreatic (5) and gastric cancer (9,11).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results from the present study indicated that plasma OLFM4 levels in breast cancer patients were associated with histological tumor differentiation. High plasma OLFM4 levels were detected in patients with high histological grade, which was consistent with data from previous studies on pancreatic (5) and gastric cancer (9,11).…”
Section: Discussionsupporting
confidence: 92%
“…A study has reported that OLFM4 levels in peripheral blood are significantly higher in gastric cancer patients prior to surgery compared with normal individuals (9). An opposite trend was observed in the present study, that is, the plasma OLFM4 expression levels were far lower in breast cancer patients compared with healthy controls.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…OLFM4 exhibited the same expression in the diverse differentiation of NSCLC and was highly expressed in tissues of NSCLC without lymph node metastasis. These observations indicated that OLFM4 may function as a tumor suppressor and an antimetastatic gene during tumor progression [24]. However, a high rate of OLFM4 overexpression was found in NSCLC patients with positive Fig.…”
Section: Discussionmentioning
confidence: 97%